Planning Algorithms to deal with Increasing Returns - Henry, C.; Zylberberg, A. (Review of Economic Studies, 1978)
C. Henry, A. Zylberberg; Planning Algorithms to deal with Increasing Returns, The Review of Economic Studies, Volume 45, Issue 1, 1 February 1978, Pages 67